2017
DOI: 10.1007/s00213-017-4633-6
|View full text |Cite
|
Sign up to set email alerts
|

Latent factor structure of a behavioral economic marijuana demand curve

Abstract: Rationale Drug demand, or relative value, can be assessed via analysis of behavioral economic purchase task performance. Five demand indices are typically obtained from drug purchase tasks. Objectives The goal of this research was to determine whether metrics of marijuana reinforcement from a marijuana purchase task (MPT) exhibit a latent factor structure that efficiently characterizes marijuana demand. Methods Participants (n=99; 37.4% female, 71.5% marijuana use days [5 days/week], 15.2% cannabis depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 49 publications
7
53
1
Order By: Relevance
“…Additional parameters were evaluated directly from the demand curve, including breakpoint (first price to suppress consumption to zero), O max (maximum expenditure), and P max (price at maximum expenditure). 2 Analyses focused on demand intensity and elasticity measures because these values generally reflect two distinct behavioral mechanisms and show separate loadings in factor analytic studies (Aston, Farris, MacKillop, & Metrik, 2017;Bidwell, MacKillop, Murphy, Tidey, & Colby, 2012;Epstein, Stein, Paluch, MacKillop, & Bickel, 2018;Murphy, MacKillop, Skidmore, & Pederson, 2009). Two approaches were used to evaluate condom purchase outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional parameters were evaluated directly from the demand curve, including breakpoint (first price to suppress consumption to zero), O max (maximum expenditure), and P max (price at maximum expenditure). 2 Analyses focused on demand intensity and elasticity measures because these values generally reflect two distinct behavioral mechanisms and show separate loadings in factor analytic studies (Aston, Farris, MacKillop, & Metrik, 2017;Bidwell, MacKillop, Murphy, Tidey, & Colby, 2012;Epstein, Stein, Paluch, MacKillop, & Bickel, 2018;Murphy, MacKillop, Skidmore, & Pederson, 2009). Two approaches were used to evaluate condom purchase outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be due partially to the curve-observed nature of P max and breakpoint, which rely on estimation from a single location on the demand curve. 4 It is also possible that imprecise 4 O max values are also curve-observed; however, the estimation of O max relies on a combination of information from the relative amplitude of consumption at low cost and the relative persistence of composition across price changes (see cross loadings for O max in factor analytical studies [53][54][55]). Intensity can also be curve-observed or derived and reflects in part the trajectory of behavior aggregated along the inelastic portion of the demand curve.…”
Section: Discussionmentioning
confidence: 99%
“…The exponentiated demand equation also provided an excellent fit to group data (fit for mean demand data R 2 : alcohol=0.99; soda=0.99) and individual data (mean of individual demand curve fits R 2 : alcohol=0.87; soda=0.91). Intensity and elasticity were selected as the primary outcomes because prior factor analytic studies have demonstrated that these measures reflect the two factors underlying the purchase task factor structure for alcohol and other substances (Aston et al, 2017; Bidwell et al, 2012; Epstein et al, 2018; MacKillop et al, 2009). Recent evidence also suggests that these derived measures show greater stimulus-selectivity than other purchase task measures (e.g.…”
Section: Methodsmentioning
confidence: 99%